Kelvin-Probe based carrier-mobility extraction reviewed by finite element simulation - Strunk, Karl-Philipp; Galow, Alexander P.; Kebrich, Sebastian; Melzer, Christian (Synthetic metals, 2019)
Periodic charging and discharging of an extended metal insulator semiconductor stack from a confined injection contact results in a lateral modulation of the carrier density. It has been demonstrated previously that this redistribution of carriers in the plane of the MIS capacitor is confined to a region near the contacts whose extension relates to the transport properties of the charged channel. Thus, monitoring the surface potential evolution with a Kelvin-Probe gives access to the transport properties of the semiconductor. Here, we investigate on the basis of 2D finite element calculations the rigidity of this proposed method. By using a bipolar drift-diffusion approach, we investigate the impact of the sample geometry, the minority and majority carrier mobility, doping, trapping and the injection properties on the extracted transport parameters. It will be shown that the proposed technique is a reliable method, which gives access to the mobility of the majority carrier species.